Enhancing Cognitive Development And Creativity Through “Tikasan” Loose Parts Media - Warning, Warning; Muhajir, Muhajir (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
The aims of this study was to determine whether the “TIKASAN” Loose Parts media can enhance cognitive development and creativity in Group B. The research employed a quantitative approach with experimental methods, utilizing a quasi-experimental design with a singular treatment model. The study population comprised children aged 5-6 years in Group B at Putra Bangsa Kindergarten. The experimental group included 15 children in Class B1 and 15 children in Class B2. This research differs from prior studies by incorporating a unique medium, “TIKASAN.”  Research data collection involved observation, documentation, and research instruments. Statistical analysis utilized parametric homogeneity tests. The results indicate that: 1) “TIKASAN” Loose Parts media significantly influences cognitive development in Group B; 2) “TIKASAN” Loose Parts media positively impacts creativity development in Group B; 3) Overall, “TIKASAN” Loose Parts media has an influence on both cognitive development and creativity in Group B.